Adaptive Emergence Patterns of Spot‐Tailed Earless Lizards: Influence of UV Light and Temperature on Diel Activity - E. Drake Rangel; Christin A. Moeller; Ruby A. Ayala; Scott E. Henke; David B. Wester; Cord B. Eversole (Ecology and Evolution, 2025)
ABSTRACT We examined the emergence behavior of spot‐tailed earless lizards (STEL; Holbrookia lacerata and H. subcaudalis). Using controlled laboratory and seminatural experiments, we evaluated the effects of UV light, visible light, temperature, and prey activity on STEL emergence timing. Our results revealed that the combination of UV and visible light was the primary trigger for STEL emergence, aligning with peak light intensity and suggesting a physiological adaptation mediated through the parietal eye. In addition, the median time of emergence was 5 min after the initiation of LED and UV lights regardless of the time of day. Peak STEL activity occurred between 14:01 and 16:00 h with nearly 50% of STEL aboveground. This delayed emergence after sunrise allows for rapid thermoregulation, minimizing basking time while reducing predation risk by avoiding periods of peak predator (e.g., birds of prey, diurnal snakes) activity, which typically occurs during early morning and late afternoon hours, which is characteristic of arid systems. Moreover, the timing likely optimizes vitamin D3 synthesis, crucial for metabolic health, and minimizes energy expenditure associated with prolonged thermoregulation. STEL's emergence patterns contrast with sympatric species, typically occurring during midday rather than early morning or late evening hours, suggesting a reliance on unique diel niches. Little is known about STEL's ecology, particularly regarding their diel niche and activity patterns, which likely play a crucial adaptive role in species survival and success. Our findings demonstrate the importance of habitat‐specific light regimes in shaping the behaviors of reptiles and provide a model for understanding adaptive strategies in light‐sensitive species. As habitat degradation and climate change alter light and thermal environments, these behaviors may be disrupted, emphasizing the need for conservation practices that preserve open, sunlit habitats. This study contributes to our understanding of the ecological adaptations of reptiles and informs conservation strategies for species in arid and semiarid ecosystems.